D-Optimal Mixture Design Enabled Development of Lyophilized Nanoemulsifying Drug Delivery System of Paliperidone - Das, Prativa; Panda, Jyanaranjan; Panigrahi, Kahnu C.; Patra, Chinam Niranjan; Jena, Goutam Kumar (Drug Delivery Letters, 2024)
Background: Schizophrenia is a chronic disease with acute psychotic symptoms, which is having frequent recurrence. Paliperidone palmitate (PP) is a second-generation antipsychotic drug to treat schizophrenia. Aims: The aim of the study was to prepare lyophilized nanoemulsifying drug delivery system (NEDDS) of paliperidone (PD). Objectives: The primary objective of the current research work was to develop a lyophilized nanoemulsifying drug delivery system (NEDDS) of paliperidone (PD) to improve its oral bioavailability and stability. Methods: Optimization using D-Optimal Mixture Design DMD) was conducted, and optimized NEDDS was further lyophilized to improve stability. The lyophilized optimized NEDDS was further evaluated for biopharmaceutical evaluation. Results: A saturation solubility study revealed Peceol, Tween 80, and Plurol Olique CC497 as suitable candidates for oil, surfactant, and co-surfactant, respectively. Optimized NEDDS of PD showed mean globule size (MGS) of 185 nm, PDI of 0.27 and cumulative % drug release within 15 min Q15 of 86.6%. Lyophilized optimized NEDDS was found to have no significant change in quality attributes within the stability study period. A pharmacokinetic study revealed more than two-fold increases in bioavailability for lyophilized optimized NEDDS. Conclusion: Hence, lyophilized NEDDS of PD can be used as an effective approach for the improvement of oral bioavailability and stability.
Keywords: lyophilized